DIASTOLIC DYSFUNCTION IN GESTATIONAL HYPERTENSION/ PREECLAMPSIA - Kjaev, Ivo; Kjaeva, Sasha; Milkovski, Daniel; Nivichka Kjaeva, Jana; Karadjova, Dafina; Aleksioska Papestiev, Irena (DEPARTMENT OF ANAESTHESIA AND REANIMATION, FACULTY OF MEDICINE, “SS. CYRIL AND METHODIUS” UNIVERSITY, SKOPJE, MACEDONIA, 2024)
Introduction: Hypertensive disorders in pregnancy including preeclampsia are present in 10% of pregnancies and are one of the biggest reasons for both maternal and fetal morbidity and mortality. Materials and Methods: The study was undertaken at the University Clinic for Gynecology and Obstetrics in Skopje, North Macedonia. After initial assessment, 81 patients were enrolled in the study after signing a written consent. Patients were divided into two groups depending on whether they had hypertension or not. In the hypertensive group 51 patients were enrolled and 30 normotensive pregnancies were used as controls. Results: Based on the values ​​of the parameters of diastolic function obtained with PDA of the transmittance flow and the values ​​of the parameters obtained with TDI of the longitudinal movement of the mitral ring, diastolic dysfunction was found in 17 (33.2%) pregnant women of the studied population, LV function (p <0.001). In the pregnant women from the examined group in whom the presence of LV diastolic dysfunction was identified, the disorders were of mild degree, that is type of delayed relaxation of LV in all 17 pregnant women. Conclusion: Early recognition and management of symptoms are essential. Women who suffer from hypertensive disorders in pregnancy require close monitoring after delivery.
Keywords: gestational hypertension; diastolic dysfunction; preeclampsia; pregnancy